Phenolic compounds, flavonoids and phenolic lipids in native Anacardiaceae from Northwest Argentina - Aristimuño Ficoseco, Maria Eugenia del Milagro (2011)
The aim of this work was to establish total contents of phenolic compounds, flavonoids and phenolic lipids in native species of Schinus and Schinopsis from northwestern Argentina. Leaves of Schinus fasciculatus, Schinus gracilipes, Schinus molle, Schinopsis haenkeana and Schinopsis lorentzii were sequentially extracted with dichloromethane (DcM), ethyl acetate (AcEt) and methanol (Met). Extracts were evaporated to dryness. Dry matter was determined and residues were dissolved in Met. Total contents of phenolic com- pounds (CFTs), flavonoids (Fs) and phenolic lipids (LFs) were de- termined by colorimetric reactions using Folin Ciocalteu, alumi- num chloride and Fast Blue B reagents, respectively. p-coumaric acid, quercetin and orcinol were used as standards. CFTs of S. haenkeana, S. gracilipes, S. molle, S. fasciculatus and S. lorentzii participated with 70, 68, 45, 43 and 20% leaf ME (p/p), respec- tively. In each plant species, contents of Fs were always higher than those of LFs. Met extracted the highest levels of CFTs, Fs and LFs. S. gracilipes and S. haenkeana had the highest contents of Fs and LFs, respectively. Phenolic compounds were found at high lev- els in ME from leaves of most Anacardiaceae investigated. They may be involved in plant defense against microorganisms.